Homology modeling and molecular dynamics study of Mycobacterium tuberculosis urease - Lisnyak, Yu; Martynov, A (Annals of Mechnikov's Institute, 2019)
Introduction. M. tuberculosis urease (MTU) is an attractive target for chemotherapeutic intervention in tuberculosis by designing new safe and efficientenzyme inhibitors. A prerequisite for designing such inhibitors is an understanding of urease'sthree-dimensional (3D) structure organization. 3D structure of M. tuberculosis urease is unknown. When experimental three-dimensional structure of a protein is not known, homology modeling, the most commonly used computational structure prediction method, is the technique of choice. This paper aimed to build a 3D-structure of M. tuberculosis urease by homology modeling and to study its stability by molecular dynamics simulations. Materials and methods.To build MTU model, five high-resolution X-ray structures of bacterial ureases with three-subunit composition (2KAU, 5G4H, 4UBP, 4СEU, and 4EPB) have been selected as templates. For each template five stochastic alignments were created and for each alignment, a three-dimensional model was built. Then, each model was energy minimized and the models were ranked by quality Z-score. The MTU model with highest quality estimation amongst 25 potential models was selected. To further improve structure quality the model was refined by short molecular dynamics simulation that resulted in 20 snapshots which were rated according to their energy and the quality Z-score. The best scoring model having minimum energywas chosen as a final homology model of 3D structure forM. tuberculosis. The final model of MTU was also validated by using PDBsum and QMEAN servers.These checksconfirmed good quality of MTU homology model. Results and discussion. Homology model of MTU is a nonamer (homotrimerofheterotrimers, (αβγ)3) consisting of 2349 residues. In MTUheterotrimer, sub-units α, β, and γ tightly interact with each other at a surface of approximately 3000 Å2. Sub-unit αcontainstheenzymeactivesitewith two Ni atomscoordinated byaminoacid residues His347, His349, carbamylated Lys430*, His459, His485, Asp 573, Gly490. Helix-turn-helix motif (residues 524-545) forms a mobile flap that covers the active site and is in closed conformation impeding access to the enzyme active site. The structural stability of MTU model was checked by molecular dynamics simulation in explicit water at 300 К and рН 7,4. During the simulation, rootmeansquaredeviationsofСαatoms (RMSD Сα)and rootmeansquare fluctuations (RMSF) ofamino acid residues of MTU were monitored for 60 ns. Also, the distance between the loop that covers the active site and the dinickel center was monitored. Analysis of MD trajectory indicate that the enzyme global structure is stable and the flap covering the active center remains in closed state during the simulation time. Conclusion.Predicted three-dimensional structure of M. tuberculosis urease can be used in the studies of structure-function relationships of the enzyme, in designing new safe and efficient enzyme inhibitors aimed to struggle with infectious diseases promoted by urease activity.